Sonovoltammetric elucidation of electron transfer rates: The oxidation of dimethyl-p-phenylenediamine in aqueous solution - Banks, C; Lawrence, N; Compton, R (2003)
The electrochemical oxidation of dimethyl-p-phenylenediamine (DMPD) in aqueous solution (pH 7 phosphate buffer) has been studied under conventional hydrodynamic and microelectrode voltammetric conditions and found to undergo a two-electron electrochemically reversible oxidation. Upon the application of ultrasound to the system an observed shoulder emerges in the oxidation wave. This effect has been attributed to the resolution of the two-electron transfer processes occurring: the first a relatively fast electron transfer (0.1 cm s-1) followed by a second slower (10-3 cm s-1) electron transfer: under the very high mass transport rates induced by insonation an overpotential develops for the second electron transfer so leading to the observed voltammetric resolution. The range of mass transport conditions accessible via sonication allows the estimation of the two rate constants reported.